Effect of a feeder layer composed of mouse embryonic and human foreskin fibroblasts on the proliferation of human embryonic stem cells - YANG, HUA (Exp Ther Med, 2016)
The aim of the present study was to investigate the effects of feeder layers composed of various ratios of mouse embryonic fibroblasts (MEFs) and human foreskin fibroblasts (hFFs) on the growth of human embryonic stem cells (hESCs). In addition, the secretion levels of basic fibroblast growth factor (bFGF) by the feeder layers was detected. MEFs and hFFs were treated with mitomycin C and seeded onto gelatin-coated plates at a density of 1×10(8) cells/l. The hFFs and MEFs were combined and plated at the following ratios: 0:1, 1:2, 1:1, 2:1 and 1:0. The secretion of bFGF by the various hFF/MEF ratio feeder layers was detected using an enzyme-linked immunosorbent assay. Subsequently, hESCs were cultured on top of the various feeder layers. The differences in the cellular morphology of the hESCs were observed using microscopy, and the expression levels alkaline phosphatase (AKP) and octamer-binding transcription factor 4 (OCT-4) were detected using immunohistochemical analysis as indicators of differentiation status. The results showed that the hFFs secreted substantial quantities of bFGF, while no bFGF was secreted by the MEFs. The clones of hESC growing on the feeder layer containing MEF or hFF alone were flat. By contrast, hESC clones grown on a mixed feeder layer containing hFFs + MEFs at a ratio of 1:1 exhibited an accumulated growth with a clear edge, as compared with the other ratios. In addition, hESCs growing on the feeder layer were positive for the expression of AKP and OCT-4. In summary, feeder layer hFFs secreted bFGF, while MEFs did not, indicating that bFGF is not the only factor that supports the growth and differentiation of hESCs. The optimal growth of hESCs was achieved using a mixed feeder layer composed of hFFs + MEFs at a ratio of 1:1.